Draft Ninth Five Year Plan 1997-2002 Tripura Part-I - Planning Commission (Planning Commission, 1997)
The Ninth Five Year Plan (1997-2002) has considerable significance in development of the country as it coincides with completion of 50 years of independence and will mark transition to the next millennium. This plan has equal importance for a small North Eastern State like Tripura, because of the multi-furious problems faced by the State. Incidentally this coincides with completion of 25 years of its attaining Statehood. Approach paper to the Ninth Plan was prepared by the Planning Commission and was discussed and approved by the National Development Council on 16th January, 97. The approach has underlined the basic need of the Ninth Plan to usher in a new era of people-oriented planning, in which people at large particularly the poor can fully participate. It has been observed that even though there has been growth in the Indian economy at the macro level, growth pattern has not equally benefitted the poor and the under privileged. The Ninth plan has therefore sought to be designed in a manner for overcoming the existing weaknesses and ensuring that benefits of the growth reach the poor.
Government of Tripura Planning & Coordination Department
Directorate of Planning
Keywords: National Perspective; State Perspective; Salient features of the State; State of Tripura’s Economy; Land Use Demography Employment; Productivity of Labour and per capita income Price; Index of relative infrastructure development; Incidence of poverty; Democratic Decentralization; Tripura Tribal Areas Autonomous District Council; Public Distribution System; New initiatives for development of the North Eastern; Financial performance; Minimum Needs Programme.